Dėl lietuviškų įrašų Krokuvos inkunabule - Zinkevičius, Zigmas (Baltistica, 2011)
LITHUANIAN GLOSSES IN THE CRACOW INCUNABULUMIn 2006, 20 Lithuanian glosses (a total of 28 words) were found in a Latin incuna-bulum at the National Museum of Cracow and published Giedrius Subačius, Mariusz Leńczuk, Wiesław Wydra, The earliest known Lithuanian glosses (~1520–1530), Archivum Lithuanicum 12, 2010, 31–70. In this article the authors’ views that the glosses should have been written in the Franciscan (Observant Bernardine) monastery of Vilnius and that the writer came from the area of the present-day West Aukštaitian Šiauliškiai are accepted; however, doubts concerning the proposed date of the glosses (1520–1530) in the 1501 Latin missal are expressed. Some aspects of the Latin orthography of the glosses of the incunabulum overlooked by the above mentioned authors are presented.
Keywords: lietuviški įrašai; Krokuvos inkunabulas